The role of TMEM59L in colorectal cancer progression and its interaction with the TGF-β/Smad pathway - Yang, Hongjie; Liu, Jiafei; Jiang, Peishi; Sun, Yi; Chen, Lingyi; Zhu, Siwei (Frontiers in Oncology, 2025)
ObjectiveThis study aimed to investigate the role of TMEM59L in colorectal cancer (CRC) and its interaction with the TGF-β/Smad signaling pathway.MethodsWe analyzed the correlation between TMEM59L expression levels and patient survival, as well as its impact on the TGF-β/Smad signaling pathway, using data from The Cancer Genome Atlas (TCGA). Additionally, transwell, CCK-8, EdU, and colony formation assays were conducted to assess the effects of TMEM59L on CRC cell migration, invasion, and proliferation. Gene silencing and overexpression, along with specific inhibitors/agonists, were used to validate the involvement of TMEM59L in the regulation of the TGF-β/Smad signaling pathway.ResultsWe found that high TMEM59L expression was associated with poor patient survival and TGF-β pathway activation. After si-TMEM59L treatment, the migration and invasion abilities of CRC cells were reduced, while cell proliferation remained affected to a lesser extent. Additionally, the levels of TGF-β protein were decreased, and the phosphorylation of Smad2/3 was reduced. In vivo, TMEM59L knockdown reduced metastatic potential as demonstrated by decreased fluorescence intensity, while overexpression of TMEM59L increased metastatic potential, which was reversed by TGF-β inhibition.ConclusionTMEM59L may promote CRC metastasis by enhancing cell migration and invasion, with minimal impact on cell proliferation, potentially through the TGF-β/Smad signaling pathway.